(Co robi) kognitywista w supermarkecie - Łukasz Afeltowicz (Avant, 2012)
[(What does) a cognitivist in the supermarket] The central area of David Kirsh’s interest is the various ways in which humans use elements of their environment as external components of computation processes or means enabling them to reduce the complexity of cognitive problems they face. in his research he performs field observations as well as laboratory experiments. Kirsh skillfully blends concepts developed in contemporary cognitive science, such as situated cognition or extended mind, with classic concepts including problem solving. A number of his theses seam to derive from “good, old fashioned” computationalism; however, this does not prevent him from demonstrating how cognitive “computations” assume not only reasonings, but also use of cognitive artifacts, bodies or the space itself. In the current issue of AVANT we present two texts authored by Kirsh.